The role of organic agriculture in sustainable development – A case study of Farah Province, Afghanistan - Noor Mohammad Kakar; Fawad Momand Omarzai (Annals of Agricultural Research, 2025)
Organic agriculture, as a sustainable production method, has garnered significant attention in recent years. This research investigates the role of organic agriculture in sustainable development by evaluating its impacts on the conservation of natural resources, reduction in chemical inputs, and improvement in the quality of agricultural products. A linear regression method was employed to analyze the data collected from a statistical population of 385 farmers actively involved in organic agriculture. The results indicate that the adoption of organic farming methods and the conservation of natural resources are significantly correlated with sustainable development. The coefficient for the adoption of organic farming methods was 0.65, and the coefficient for the conservation of natural resources was 0.55, demonstrating a positive and substantial influence of these factors on sustainable development. Furthermore, the use of natural fertilizers showed a significant impact on sustainable development with a coefficient of 0.40. In contrast, the reduction in pesticide use had a minimal and statistically insignificant impact on sustainable development (coefficient of 0.15). The ANOVA test revealed that the regression model is statistically significant overall, explaining 63% of the variance in sustainable development. Based on these findings, organic agriculture, through the conservation of natural resources, reduction in chemical use, and improvement in product quality, can play a crucial role in achieving sustainable development goals.